Latent profiles of elite Malaysian athletes' use of psychological skills and techniques and relations with mental toughness - Ponnusamy, V.; Lines, Robin; Zhang, C.; Gucciardi, Daniel (PeerJ, Ltd., 2018)
© 2018 Ponnusamy et al. Background: The majority of past work on athletes' use of psychological skills and techniques (PSTs) has adopted a variable-centered approach in which the statistical relations among study variables are averaged across a sample. However, variablecentered- analyses exclude the possibility that PSTs may be used in tandem or combined in different ways across practice and competition settings. With this empirical gap in mind, the purposes of this study were to identify the number and type of profiles of elite athletes' use of PSTs, and examine differences between these clusters in terms of their self-reported mental toughness. Methods: In this cross-sectional survey study, 285 Malaysian elite athletes (170 males, 115 females) aged 15-44 years (M = 18.89, SD = 4.49) completed measures of various PSTs and mental toughness. Latent profile analysis was employed to determine the type and number of profiles that best represent athletes' reports of their use of PSTs in practice and competition settings, and examine differences between these classes in terms of self-reported mental toughness. Results: Our results revealed three profiles (low, moderate, high use) in both practice and competition settings that were distinguished primarily according to quantitative differences in the absolute levels of reported use across most of the PSTs assessed in practice and competition settings, which in turn, were differentially related with mental toughness. Specifically, higher use of PSTs was associated with higher levels of mental toughness. Conclusion: This study provides one of the first analyses of the different configurations of athletes' use of PSTs that typify unique subgroups of performers. An important next step is to examine the longitudinal (in) stability of such classes and therefore provide insight into the temporal dynamics of different configurations of athletes' use of PSTs.